Right gyrus cinguli low-grade astrocytoma recurrence removed through a contralateral transfalcine approach with a 4K-3D exoscope - Stefano Peron; Giovanni Marco Sicuri; Andrea Cividini; Roberto Stefini (Chinese Neurosurgical Journal, 2023)
Abstract Background Brain tumor surgery has been using operative microscope for years. Recently, thanks to developments in surgical technology with procedures performed on head-up displays, exoscopes have been introduced as an alternative to microscopic vision. Case presentation We present a case of a 46-year-old patient with a low-grade glioma recurrence of the right gyrus cinguli removed with a contralateral transfalcine approach using an exoscope (ORBEYE 4K-three-dimensional (3D) exoscope, Sony Olympus Medical Solutions Inc., Tokyo, Japan). The operating room setup for this approach is illustrated. During the procedure, the surgeon was seated with head and back in an upright position, while the camera was aligned with the surgical corridor. The exoscope provided detailed, high-quality 4K-3D images of the anatomical structures and optimal depth perception, making surgery accurate and precise. At the end of the resection, an intraoperative MRI scan showed complete removal of the lesion. The patient was discharged on postoperative day 4 with an excellent performance on neuropsychological examination. Conclusions In this clinical case the contralateral approach was favorable because the glioma was located close to the midline and because it offered a straight path to the tumor, minimizing retraction on the brain. The exoscope provided the surgeon with important advantages in terms of anatomical visualization and ergonomics during the entire procedure.